Genome-wide profiling reveals novel microRNAs in hand-spinning-specific chrysotile exposure. (21st January 2019) - Jia, Junlin; Guo, Xinnian; Feng, Lingfang; Yin, Xianhong; Zhu, Lijin; Li, Jinhao; Yu, Dandan; Fang, Yuan; Jiang, Zhaoqiang; Yu, Min; Xia, Hailing; Shi, Li; et al.
Aim: We aimed to explore miRNA expression profiles in hand-spinning chrysotile exposed workers and their potential influencing factors.Methods: miRNA array technique was applied to screen differentially expressed miRNAs between plasma samples from three exposed workers and three controls. Then, seven selected miRNAs were validated in 143 workers and 100 controls, and the potential influencing factors were revealed by multiple linear regression. Finally, the expression levels of those seven miRNAs were evaluated in human mesothelial cells (Met-5A) that were exposed to chrysotile at 5 μg·cm -2 for 8, 24 and 48 h, respectively.Results & conclusion: Hand-spinning chrysotile exposure can result in differential expression of miRNAs. Several of those miRNAs have positive correlations with asbestos exposure.